Knotted or knotless double-row rotator cuff repair retear rates: a systematic review and meta-analysis - Figueiredo, JA (2024)
Background: Arthroscopic rotator cuff tear repair techniques used to rely on knot-tying double row techniques, but the advent of knotless transosseous equivalent procedures introduced a new variable to the debate. The purpose of this study is to determine which technique is associated with lower retear rates. For its' biomechanical advantages, the authors' hypothesis is that knotless techniques would have lower retear rates. Methods: A systematic literature search was performed via PubMed and Google Scholar by two independent reviewers following PRISMA guidelines. Papers reporting retear rates after rotator cuff arthroscopic repair using knotted double-row or knotless transosseous equivalent techniques, evaluated by magnetic resonance imaging at least 6 months after surgery, were retrieved. Studies that do not differentiate between techniques and nonclinical reports were excluded. Eligible data was analyzed with Review Manager 5.4.1 using Mantel-Haenszel statistics with a fixed effect model. Results: The authors' initial literature search retrieved 511 reports. After the selection process, 24 articles were available for this review, and 9 were eligible for meta-analysis. A comparison of 1888 subjects from noncomparative reports and a meta-analysis of reports in which both techniques were studied could not show a statistically significant difference in technique retear rates. Discussion and conclusion: The current report revealed no significant difference in retear rates between the two arthroscopic repair techniques. Studies' quality was a limitation. Only two reported level 1 evidence. This review could not control variables such as cuff tear size, tissue quality, or individual comorbidities. Larger and longer follow-up studies could be helpful to further investigate this topic.